A novel lead-based pseudo dimensional stable anode toward efficient and clean extraction of metallic manganese. (1st February 2023) - Tang, Binyuan; Yang, Fan; Chen, Chaoyi; Shi, Changping; Deng, Wei; Li, Junqi; Jiang, Liangxing
Abstract: Although the application of the dimensionally stable anode (DSA) is of great value to meet the environmental demands for sustainable development of electrometallurgy, the unsatisfactory stability and high-costs hinder its industrialization in Mn metallurgy. Hereby, a novel lead-based pseudo dimensional stable anode (LBP-DSA) was proposed firstly to overcome the intrinsic defects of the lead-based anodes and inherit the advanced characteristics of the DSA. The unique advantage for the hierarchical skeleton of LBP-DSA (lead-based/TiB2 /γ-MnO2 ) was discussed in detail. To begin with, a sufficiently robust lead-based/TiB2 substrate was constructed to eliminate the lead pollution in electrolysis system. The key role of TiB2 interlayer was devoted to solidify the lead substrate and provide suitable anchors for subsequent layer adhesion. Subsequently, the as-synthesized γ -MnO2 on different substrates were comparatively analyzed to highlight that the tantalizing oxygen evolution selectivity relied on screening the lead pollution in γ -MnO2 lattice. Beneficial from the synergistic effects of TiB2 with γ -MnO2, our LBP-DSA exhibited a great potential in energy-saving and hazardous anode slime reduction. The satisfactory long-term stability and corrosion resistance made the LBP-DSA as a promising candidate for cleaner production of metallic manganese. Graphical abstract: The lead-based pseudo dimensional stable anode was applied to manganese electrowinning process, and the energy consumption and hazardous anode slime were reduced under the synergistic effects of TiB2 with MnO2 . Image 1